Development of the Indonesian Version of the Object-Spatial Imagery and Verbal Questionnaire (IDN-OSIVQ) - Fatimatul Khikmiyah; Tatag Yuli Eko Siswono; Agung Lukito (Journal An-Nafs: Kajian Penelitian Psikologi, 2024)
Developing the Indonesian Version of the Object-Spatial Imagery and Verbal Questionnaire (IDN-OSIVQ) aims to create a culturally adapted and validated instrument for assessing object-spatial imagery abilities in the Indonesian population. The research utilized a developmental method to test the instrument's reliability and validity through rigorous adaptation procedures, including translation, back-translation, expert review, and pilot testing. Data from 153 students were analyzed to establish the internal consistency, construct validity, and factor structure of the IDN-OSIVQ. Results showed that the IDN-OSIVQ scales had satisfactory internal reliability, with principal component analysis confirming distinct and coherent factors. Object imagery had the highest average score (3.6662), while spatial imagery had the lowest (3.1765). Criterion validity was established as participants' ratings correlated favorably with corresponding tasks. Gender differences were observed: men scored higher on spatial imagery and women on object imagery, yet these differences did not overshadow the strong associations between cognitive style ratings and objective measures. The cultural adaptation process ensured the questionnaire's relevance and comprehensibility, enhancing its applicability. The findings support the IDN-OSIVQ as a reliable and valid tool, suggesting future research should involve more diverse age groups.